Tratamento de efluente de biodiesel pela integração dos processos de coagulação-floculação, UV-C e oxidação avançada - Costa, Nayara de Melo (2018)
Considering a large amount of wastewater generated in the production of biodiesel and high amount of contaminants present in the effluent, in this work, the integration of the coagulation-flocculation process with the direct UV-C and advanced oxidation processes (H2O2/UV-C and photo-Fenton) to improve organoleptic properties and reduce the organic load and toxic levels of the crude biodiesel effluent. Coagulation-flocculation process was applied as a pretreatment, aiming at the maximum turbidity removal efficiency of the effluent, where different iron salts (Fe(NO3)3, FeCl3 and Fe2(SO4)3) and concentrations (0.25, 0.50 and 1.0 mmol L-1) were evaluated. The best results were obtained with 0.5 mmol L-1 of Fe(NO3)3, which resulted in a 99% removal of turbidity at the natural effluent pH (2.9). However, this process was inefficient to remove the organic fraction and toxicity solution, being to need the integration with other processes such as UV-C, H2O2/UV-C and photo-Fenton. Among the evaluated conditions, in the H2O2/UV-C process, the application of 4000 mg L-1 of H2O2 in sequential addition of 2000 mg L-1 with irradiation time between 4 and 6 hours, was ideal for a complete treatment, where a high mineralization efficiency (94%) was obtained and a reduction close to 70% of the acute toxicity to V. fischeri was achieved. On the other hand, in order to reduce costs with chemical reagents, the application of the UV-C process during 6 hours is recommended as a pre-treatment for subsequent coupling with a biological process, where the toxicity reduced from 89% to 22% generating a BOD5/COD equivalent to 0.44. The classical photo-Fenton process presented low efficiency in the removal of the soluble organic fraction from the pretreated effluent due to the formation of stable and soluble complexes between the organic pollutants and ferrous ions, reducing the iron concentration in the medium and, consequently, inhibiting the production of hydroxyl radicals. On the other hand, a positive synergism in organic matter removal was observed in the modified photo-Fenton experiment, using multiple additions of the oxalate complexing agent, which avoided the formation of complexes with the organic pollutants and increased the quantum yield of ferrous ions and hydroxyl radicals. The application of 1.0 mmol L-1 of ferrioxalate contributed to the reduction of the COD at 70% and BOD5 at 76% after a UVA dose of 602 kJ m-2, with simultaneous reduction of the acute toxicity to Vibrio fischeri from 70% to 6%.